From the gold rush to the urban crush: the past, present and future of the South Platte River Basin - Brown, Jennifer, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2006)
Abstracts of papers presented at the 17th annual South Platte Forum held on October 25-26, 2006 at the Radisson Conference Center in Longmont, Colorado.
October 2006.
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water -- Law and legislation -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water use -- South Platte River Valley (Colo. and Neb.) -- Congresses